2002
DOI: 10.1034/j.1600-0404.2002.1o077.x
|View full text |Cite
|
Sign up to set email alerts
|

Varicella, ephemeral breastfeeding and eczema as risk factors for multiple sclerosis in Mexicans

Abstract: During the last decades, breastfeeding has been abandoned in large segments of society and the incidence of varicella and childhood eczema keeps a north-south gradient similar to that described for MS. These factors may participate in the sharp increase of MS in countries like Mexico traditionally considered as an area of very low incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
1
32
1
Order By: Relevance
“…On the other hand, no difference was found in our study with respect to type of residence, corroborating the findings of Granieri and Casetta 7 . Other factors, such as artificial baby milk 16 and a predominance of meat and animal fat in the diet 4,15 , have been associated with this illness; however, these findings were not confirmed in the present study nor in the one conducted by Kurtzke and Page 8 .…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…On the other hand, no difference was found in our study with respect to type of residence, corroborating the findings of Granieri and Casetta 7 . Other factors, such as artificial baby milk 16 and a predominance of meat and animal fat in the diet 4,15 , have been associated with this illness; however, these findings were not confirmed in the present study nor in the one conducted by Kurtzke and Page 8 .…”
Section: Resultscontrasting
confidence: 57%
“…Although this hypothesis had been raised by Tarrats et al 16 in a Mexican study, these authors found no association between ingestion of pig or bovine brain and MS. Contact with animals (dogs, birds and farm animals) was found to be associated with the disease according to reports published by Bobowick et al 13 , Bansil et al 6 and Ghadirian et al 9 .…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…There have been many reports suggesting an association between one or more of these infectious diseases and MS [15,16] , but these were not confirmed in a larger registry-based study [17] . However, evidence is growing that a history of infectious mononucleosis is associated with susceptibility to MS [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 97%
“…For instance, optic neuritis represents 12% of the patients referred to a specialized neuro-ophthalmology clinic [12] ; about 40% of them are eventually diagnosed as having MS [12,13] . Potential risk factors responsible for the increase in MS in Mexico include a decrease in breastfeeding for large segments of the society and an increased incidence of varicella and childhood eczema [14] . Research conducted at the National Institute of Neurology and Neurosurgery of Mexico has demonstrated activation of varicella-zoster virus during MS relapses [15] , suggesting that this herpes virus could be an etiological agent of MS.…”
mentioning
confidence: 99%